Right ventricular pressure–volume relations and effects of selective vena cava occlusion during cardiopulmonary resuscitation - Woo Jin Jung; Young-Il Roh; Soyeong Kim; Hyeonyoung Im; Yujin Lee; Sooyoung Sung; Jae Hun Han; Kyoung-Chul Cha; Sung Oh Hwang (PLoS ONE, 2025)
Objectives To investigate right ventricular hemodynamics and determine how vena cava occlusion (VCO) influences right ventricular pressure–volume dynamics during cardiopulmonary resuscitation (CPR). Methods We used a swine model of electrically induced ventricular fibrillation. Five animals were allocated to Experiment I to observe right ventricular hemodynamics during standard CPR, and 25 were assigned to Experiment II to assess right ventricular hemodynamic changes following VCO. In Experiment I, all animals received standard CPR. In Experiment II, all animals received CPR but were randomized according to the protocols used, which differed by the order of interventions. The interventions included alternating superior VCO, inferior VCO, and no VCO. Hemodynamic parameters were measured during CPR, and corresponding right ventricular pressure–volume loops were generated. Results Experiment I revealed that, during CPR, the right ventricular pressure–volume loop became trapezoidal in shape, with a progressive reduction in right ventricular volumes, including end-systolic volume (p = 0.029) and end-diastolic volume (p = 0.035). Experiment II demonstrated that systolic arterial pressure and end-tidal CO₂ levels were significantly lower during both superior and inferior VCO CPR than during no-VCO CPR (both p < 0.001). During superior and inferior VCO CPR, both end-systolic and end-diastolic right ventricular pressures were also significantly lower than those during no-VCO CPR (p < 0.001 and p = 0.003, respectively). Right ventricular stroke volumes did not differ significantly across the three VCO conditions. The shapes and values of right ventricular pressure–volume loops were relatively similar across the three VCO conditions. Conclusions During CPR, the right ventricular pressure–volume loop transforms into a trapezoidal shape, resembling a left-leaning triangle, because the isovolumetric phases disappear. VCO during CPR reduces ventricular systolic pressures, indicating that a reduction in the venous return affects perfusion pressures during resuscitation.